RELIGIOUS MODERATION: FUTURE GENERATIONS THROUGH DAYAH EDUCATION IN COMMUNITY DEVELOPMENT - abdul Razak; Aiyub Bardan; akmal Fajri (STAI Nusantara Kota Banda Aceh, 2024)
Future generations are a crucial pillar of society. They will become leaders and take charge of societal development. Therefore, preparing the younger generation is essential, especially through dayah educational institutions. As the oldest religious education institutions operating within Indonesian society, dayah institutions face numerous challenges in adapting to the digital era. These challenges include preparing the younger generation to keep up with modern developments and becoming agents of community development. This article employs qualitative research methods to address these issues, using observation and analytical studies of relevant documentation. The findings suggest that dayah educational institutions need to modernize their systems by integrating technological advancements and preparing adequate resources to support their educational missions. Additionally, incorporating religious moderation into the curriculum is necessary to foster tolerance and appreciation for diversity among the younger generation. This approach aims to safeguard them from the influence of hoaxes disseminated by irresponsible parties via social media and the internet, which could disrupt societal unity. Keywords: Future generation, dayah educational institutions, digital era, religious moderation, tolerance, societal unity.